Escherichia coli outer membrane vesicles can contribute to sepsis induced cardiac dysfunction - Kristina Svennerholm (Nature Portfolio, 2017)
Abstract Sepsis induced cardiac dysfunction (SIC) is a severe complication to sepsis which significantly worsens patient outcomes. It is known that bacteria have the capacity to release outer membrane vesicles (OMVs), which are nano-sized bilayered vesicles composed of lipids and proteins, that can induce a fatal inflammatory response. The aim of this study was to determine whether OMVs from a uropathogenic Escherichia coli strain can induce cardiac dysfunction, and to elucidate any mechanisms involved. OMVs induced irregular Ca2+ oscillations with a decreased frequency in cardiomyocytes through recordings of intracellular Ca2+ dynamics. Mice were intraperitoneally injected with bacteria-free OMVs, which resulted in increased concentration of pro-inflammatory cytokine levels in blood. Cytokines were increased in heart lysates, and OMVs could be detected in the heart after OMVs injection. Troponin T was significantly increased in blood, and echocardiography showed increased heart wall thickness as well as increased heart rate. This study shows that E. coli OMVs induce cardiac injury in vitro and in vivo, in the absence of bacteria, and may be a causative microbial signal in SIC. The role of OMVs in clinical disease warrant further studies, as bacterial OMVs in addition to live bacteria may be good therapeutic targets to control sepsis.